The Broken Thread of Asian Culture (Asian Journal of Social Science Studies, 2018)
Sociobiology derives its atheistic stance from the Darwinian framework of purposeless, naturally selections of random variations of matter in motion. However, explanatory gaps in sociobiology’s explanation of religion, from the initial cosmic singularity to free will, invite a Divine foot in the door. By interpreting yogic, Taoist and Kabbalistic descriptions of the anatomical connection between the human and the divine not as primitive, poetic metaphors but as interoceptions of a little-known, enigmatic, epigenetically suppressed, structure running through the central axis of the central nervous system called Reissner’s fiber. I propose a new theistic sociobiological theory of religion. Justified belief in this theory could epigenetically reawaken the suppressed Reissner’s fiber genes and begin the empirical testing of the theory.